PROJECT-BASED ASSESSMENT FOR ESP (ENGLISH FOR SPECIFIC PURPOSE) STUDENTS: LECTURERS' PERSPECTIVE - Marina Marina; Muhammad Roni; Mursidah Mursidah (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This paper examines lecturers' perceptions of the project-based learning model and assessment on the teaching of English Accounting at the Faculty of Economics and Business, Malikussaleh University. Project-based Learning (PBL) is one of the Merdeka Belajar priority program plans in 2021 which is part of the Kampus Merdeka plan by the Ministry of Education and Culture and Higher Education. Projects in education are one of the assessment instruments used to assess not only learning outcomes but also student learning processes. Students are required to not only learn to understand the material but also learn how to apply knowledge in group work and produce relevant products. The purpose of developing a project-based learning model for accounting students studying English for specific purpose (ESP) is so that they can apply English knowledge to their field of expertise, namely accounting.